Suppurative coxitis due to Salmonella typhimurium in systemic lupus erythematosus. Issue 3 (June 1981) - Shiota, K; Miki, F; Kanayama, Y; Kohno, M; Ohe, A; Takamatsu, K; Inoue, T
Abstract : A 36-year-old woman with systemic lupus erythematosus (SLE) developed septicaemia and subsequently suppurative coxitis due to Salmonella typhimurium. Although systemic treatment with antibiotics eradicated salmonella from the arterial blood, cup arthroplasty and irrigation of the operative wounds with effective antibiotics were needed for eradication of the organism from the affected joints.